A linguistic account of Business English - Potęga, Paulina (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
Business English is a rapidly growing field of language study which concerns an increasing number of scholars. In short, it is associated with specialised area of English related to the language employed in all types of business contexts. Therefore, a new and urgent need for not only practical applications of Business English has appeared, but also its theoretical accounts that opens new opportunities and research vistas. Although the term itself has long been the subject of interest of academics and language teachers, the concept still seems to pose a number of controversies and frequently leads to confusion. In this paper an attempt will be made to shed some light on the linguistic structure of Business English by identifying its main features and providing an overview of the area, especially in the field of grammar and vocabulary.
Keywords: Business English; specialist language; grammar; vocabulary